Can supplementary private health insurance further supplement health - Chen, Xinlin; Guo, Dandan; Tan, Huawei; Zhang, Yunfan; Liu, Yanchen; Chen, Xinlan; Chen, Yingchun (Frontiers in Public Health, 2022)
Background: China advocates a health insurance system with social health insurance (SHI) as the main body and private health insurance (PHI) as the supplement. The study of PHI’s complementary role in health is conducive to providing evidence for PHI’s policy expansion and encouraging the public to participate in PHI, which is insufficient in China. Methods: We used the three-wave balanced panel data of the China Health and Retirement Longitudinal Survey (CHARLS). Taking the ownership of supplementary PHI as the independent variable and EQ-5D index scores as the dependent variable, the panel instrumental variable (IV) method was used to analyze the impact of participation in PHI on health. We also assessed the heterogeneity of the health effects of PHI between chronic and non-chronic disease groups and between low- and high-income groups. Results: The coverage rate of PHI at baseline was 10.53%. The regression results showed that participating in PHI on the basis of SHI could result in an additional 8.21% health gain (P<0.001). At the same time, PHI had greater health gain for chronic disease population than for healthy population (9.25% vs 6.24%, P<0.001), and greater health gain for high-income population than for low-income population (8.32% vs 5.31%, P<0.001). Conclusion: Participating in supplementary PHI can effectively enhance the health status of the insured, and has a more significant effect on patients with chronic diseases. The development of PHI should be further supported, while the health inequality in different income groups should be paid attention to.